Fine Mapping the Interaction Between Dendritic Cell-Specific Intercellular Adhesion Molecule (ICAM)-3-Grabbing Nonintegrin and the Cytomegalovirus Envelope Glycoprotein B. (10th April 2018) - Chéneau, Coraline; Coulon, Flora; Porkolab, Vanessa; Fieschi, Franck; Laurant, Stéphanie; Razanajaona-Doll, Diane; Pin, Jean-Jacques; Borst, Eva Maria; Messerle, Martin; Bressollette-Bodin, Céline; Halary, Franck
Abstract : The envelope glycoprotein B of the human cytomegalovirus is a ligand for the lectin DC-SIGN. Here, the authors characterized this interaction at the molecular level. This should help to design new specific antiviral drugs. Abstract: Background: Human cytomegalovirus (HCMV) is a leading cause of virally induced congenital disorders and morbidities in immunocompromised individuals, ie, transplant, cancer, or acquired immune deficiency syndrome patients. Human cytomegalovirus infects virtually all cell types through the envelope glycoprotein complex gH/gL/gO with or without a contribution of the pentameric gH/gL/pUL128L. Together with gH/gL, the HCMV envelope glycoprotein B (gB) contributes to the viral fusion machinery. Methods: We previously showed that gB is a ligand for the C-type lectin dendritic cell-specific intercellular adhesion molecule-3-grabbing nonintegrin (DC-SIGN) contributing to HCMV attachment to and infection of DC-SIGN-expressing cells. However, the features of the DC-SIGN/gB interaction remain unclear. To address this point, the role of glycans on gB and the consequences of mutagenesis and antibody-mediated blockades on both partners were examined in this study. Results: We identified DC-SIGN amino acid residues involved in this interaction through an extensive mutagenesis study. We also showed the importance of high-mannose N -glycans decorating the asparagine residue at position 208, demonstrating that the antigenic domain 5 on gB is involved in the interaction with DC-SIGN. Finally, antibody-mediated blockades allowed us to identify DC-SIGN as a major HCMV attachment receptor on monocyte-derived dendritic cells. Conclusions: Taken together, these results have permitted us to fine-map the interaction between DC-SIGN and HCMV gB.